A novel assay for exosomal and cell-free miRNA isolation and quantification. Issue 4 (2nd April 2020) - Grunt, Magdalena; Failla, Antonio Virgilio; Stevic, Ines; Hillebrand, Timo; Schwarzenbach, Heidi
ABSTRACT: The use of disease-specific signatures of microRNAs (miRNAs) in exosomes has become promising for clinical applications, either as biomarkers or direct therapeutic targets. However, a new approach for exosome enrichment and quantification of miRNAs is urgently needed for its clinical application, since the commercial techniques have shortcomings in quantity and quality. To overcome these deficiencies, we developed a new method for purification of exosomes with subsequent miRNA extraction, followed by quantitative reverse transcription polymerase chain reaction (RT-qPCR), and compared our assays with commercial techniques. For the establishment of these methods, numerous reagents, parameters, and combinations thereof were examined. Our new technique for exosome extraction is based on a mannuronate-guluronate polymer (MGP) which avoids co-precipitating plasma proteins. Quality, concentration and biological activity of the isolated exosomes were examined by Western blot, Nanoparticle Tracking Analysis (NTA), and confocal microscopy. A combination of chaotropic and non-chaotropic salts was used to extract miRNAs from plasma, serum, and exosomes, allowing the exclusion of hazardous components, such as phenol/chloroform. The performance of the miRNAs extraction was verified by RT-qPCR. The chemistry and TaqMan probe were also optimized for RT-qPCR. Sensitivity, efficiency, and linearity of RT-qPCR were tested on serial dilutions of synthetic miR-16 and miR-142. Our established procedure covers all steps of miRNA analyses, and measures the levels of either cell-free and exosomal miRNAs in plasma, serum and other body fluids with high performance.